Modulated effectiveness of rehabilitation motivation by reward strategies combined with tDCS in stroke: study protocol for a randomized controlled trial - Zhou, Ping; Li, Wenxi; Zhao, Jingwang; Chen, Siyun; Chen, Yufeng; Shen, Xia; Xu, Dongsheng (Frontiers in Neurology, 2023)
Background：Stroke survivors often exhibit low rehabilitation motivation, hindering their ability to effectively complete rehabilitation training task effectively and participate in daily activities actively. Reward strategies have been identified as an effective method for boosting rehabilitation motivation, but their long-term efficacy remains uncertain. tDCS has been recognized as a technique that facilitates plastic changes and functional reorganization of cortical areas.Particularly, tDCS can improve the functional connectivity between brain regions associated with goal-directed behavior when applied to dlPFC. Combing reward strategies with tDCS (RStDCS) has been shown to motivate healthy individuals to exert more effort in task performance. However,research exploring the combined and sustained effects of these strategies on rehabilitaion motivation in stroke survivors is lacking. Methods and Design： Eighty-seven stroke survivors with low motivation and upper extremity dysfunction will be randomized to receive either conventional treatment , RS treatment, or RStDCS treatment. The RStDCS group will receive reward strategies combined with tDCS stimulation on left dlPFC. The RS group will receive reward strategies combined with sham stimulation. The conventional group will receive conventional treatment combined with sham stimulation. tDCS is performed over 3 weeks of hospitalization, 20 minutes/time, 5 times a week. Reward strategies refers to personalized active exercise programs for patients during hospitalization and at home. Patients can voluntarily choose tasks for active exercise and self-report to the therapist so as to punch a card for points and exchange gifts.The conventional group will recieve home rehabilitation instructions prior to discharge. Rehabilitation motivation, measured using RMS. RMS,FMA, FIM and ICF activity and social engagement scale will be compared at baseline, three weeks, six weeks, and three months post-enrollment to evaluate patients’ multifaceted health condition based on ICF framework. Disscussion：We utilize multidisciplinary，straightforward and feasible reward strategies, combined with neuromodulation technology, to jointly improve patients' rehabilitation motivation. Behavioral observations and various assessment tools are used to monitor rehabilitation motivation and multifaceted health condition according to the ICF framework. The aim is to provide a preliminary exploration path for professionals to develop comprehensive strategies for improving rehabilitation motivation, facilitating a complete "hospital - home - society" rehabilitation process. Trial registration number: [https://www.chictr.org.cn/showproj.aspx?proj=182589], identifier [ChiCTR2300069068]